Pengaruh Pelatihan Terhadap Pengetahuan Tentang Gizi Buruk dan Inter-Professional Collaboration Petugas Puskesmas - Ghusta Dzakki Andita Pratama; Luthfiana Faliza Nur Arifa; Sabrina Fadilah Diana Danifah; Steffy Desiandra Puteri; Liss Dyah Dewi Arini (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Very complex health problems require treatment involving all health professionals. The nutritional status of children is one of the important things to prepare a quality generation. Health education in the form of training is expected to change the competence of collaboration across healthcare professionals. The aim of the study was to determine the effect of training on health workers on knowledge about malnutrition and collaboration across professions. This study uses a Mix-Method approach with triangulation techniques using a questionnaire for qualitative stages by conducting a content analysis and on a quantitative stage using the research design method "Pre Experiment" with a research design using "one group pre and post-test design". Test for normality using Shapiro -Wilk. Statistical analysis using the Wilcoxon test and paired T-test. The Results showing are analysis content informs that the training has been going well and is able to increase participants' knowledge. Statistical test results show that nutrition knowledge before training has a mean of 4.50 and after training has a mean of 4,467. This does not show an increase in average. The results of the statistical test, namely the test T-test showed p- value = 0.586 (p> 0.05) which means that there is no difference in mean knowledge about nutrition before and after treatment. As for knowledge about collaboration before training has a mean of 8.75 and after training has a mean of 10.67. This shows an increase in average. Statistical test results show p-value = 0.008 (p <0.05) which shows that there is a difference in mean knowledge about collaboration before the treatment in the module testing group. So, Cross-professional collaboration training in handling malnutrition affects changes in health worker knowledge. There are differences in changes in knowledge of malnutrition and collaboration across professions before and after training.